SABBATAI ZEVI: TURKEY'S ENIGMATIC MESSIAH - Himam, Mohammad Muafi (UIN Sunan Kalijaga Yogyakarta, 2025)
This study examines the life and spiritual phenomenon of Sabbatai Zevi, a 17th-century Jewish figure who claimed to be the Messiah and significantly influenced Jewish communities in Turkey and beyond. The academic problem addressed in this study is the historical and theological controversy surrounding Zevi’s messianic claims and their socio-religious impact. The methodology used in this research involves a historical analysis of primary and secondary sources, along with a literature review of existing studies on Zevi. The theoretical framework is based on religious mysticism and messianic movements within Jewish traditions, particularly the Kabbalistic interpretation of the Messiah. The results reveal the complexity of Zevi’s identity, his impact on Jewish and Ottoman societies, and the transformation of his movement after his forced conversion to Islam. The study concludes that Zevi’s influence persists through the Dönmeh community, whose secret religious practices continue to be a subject of scholarly debate. Keywords: Sabbatai Zevi, Dönmeh, Jewish Mysticism, Ottoman Empire Penelitian ini mengkaji kehidupan dan fenomena spiritual Sabbatai Zevi, tokoh Yahudi abad ke-17 yang mengklaim sebagai Mesias dan membawa pengaruh besar terhadap komunitas Yahudi di Turki dan sekitarnya. Masalah akademik yang dibahas dalam penelitian ini adalah kontroversi sejarah dan teologis terkait klaim mesianis Zevi serta dampaknya terhadap masyarakat sosial-keagamaan. Metodologi yang digunakan adalah analisis historis terhadap sumber primer dan sekunder, serta tinjauan literatur terhadap penelitian yang telah dilakukan mengenai Zevi. Kerangka teori dalam penelitian ini berpusat pada mistisisme agama dan gerakan mesianis dalam tradisi Yahudi, khususnya interpretasi Kabbalistik tentang Mesias. Hasil penelitian menunjukkan kompleksitas identitas Zevi, dampaknya terhadap masyarakat Yahudi dan Utsmani, serta transformasi gerakannya setelah dipaksa masuk Islam. Studi ini menyimpulkan bahwa pengaruh Zevi tetap bertahan melalui komunitas Dönmeh, yang praktik keagamaannya masih menjadi perdebatan akademik hingga kini. Kata kunci: Sabbatai Zevi, Donmeh, Mistisisme Yahudi, Kesultanan Utsmaniyah